Intelectuais orgânicos no desenvolvimento territorial solidário e contra-hegemônico: o caso do banco Palmas - Carvalho, Hilano José Rocha de (2017)
The capitalist social formation imposes to all the relations among the people the domination of the economic and material dimension. Freedom in the democratic social forms in which capitalist social relations reign does not go beyond the right to intensify the processes of production and consumption by a dominant minority. From this, it results a permanent confrontation of ideological forms and between opposing social groups: on the one hand, those who act to maintain intact hierarchical relations and the exploitation of work; on the other hand, those who construct a new kind of plural, solidary and emancipated society. In this scenario, Solidarity Economy emerges as the economic, social, cultural and alternative political base, identified with initiatives based on solidarity, cooperation and self-management. From the solidary economic initiatives, in solidarity finance, the Community Development Banks (CDBs) spread through Brazilian territories from local development. The work of the CDBs goes far beyond the generation of work and income, as it promotes qualitative social changes of a cultural and political character in the territories in which they arise. The objective of this work was to identify the necessary, sufficient and favorable conditions, the difficulties and the limits for the long-term development of the BCDs, in the promotion of the territorial development of solidarity and counter-hegemonic. For this, as an empirical object, the pioneering experience Banco Palmas (located in Palmeiras, Fortaleza-CE, Brazil) was defined as the unique and decisive case. Two theoretical-conceptual and methodological perspectives were taken as basilar, resulting in the formulation of corresponding hypotheses: a) from the conceptual framework of Gramscian political theory, Banco Palmas was analyzed in the relations between internal and external social actors and between social forces and policies in the face of the processes of hegemony and domination; b) from the controversies between social management and strategic management and the conceptual debate of strategy in the context of the Solidarity Economy, the Palmas Bank, the strategic management and planning forms in Solidarity Economy and its effects on the development of the Palmeiras territory were analyzed. The hypotheses were formulated from a method of articulation between evidences, theoretical-conceptual referential and hypotheses, which also guided the collection and analysis of data. The data collection was done by bibliographical research of publications of previous studies and documentary research. For the analysis of the data, the technique of adaptation to the standard and the analysis of time series (in the case of social and financial-economic indicators) were used. As a result, Banco Palmas' strategic management and planning actions are approaching communicative and non-strategic-instrumental social actions, such as social technologies, insofar as they involve the Palmeiras community in interaction and dialogue with various social actors. These actions are coordinated by the organic intellectuals present at Banco Palmas, counting on the solidarity, support and alliance with organic intellectuals of higher social strata with civil society and the State, being the necessary and essential conditions for the long-term development of the Banco Palmas. With this work, it is hoped to contribute to the emergence of a Solidarity Economy praxis centered on a territorial development that is solidary and counter-hegemonic, as it was found, even if embryonically, in the case of Banco Palmas.